The Influence of Good Corporate Governance Dimension on Financial Performance: The Intervening Effect of Capital Structure - Efionita, Yolanda; Ratnawati, Kusuma; Indrawati, Nur Khusniyah (Jurnal Aplikasi Manajemen, 2025)
This study explores the indirect association connecting good corporate governance dimensions and firm performance, mediated through capital structure. This study utilized a sample of 67 manufacturing companies registered on the Indonesian Stock Exchange from 2014 to 2017. The data was also handled using the Eviews 10.0 version. The findings show that board of director size, board independence, managerial ownership, and ownership concentration showed no impact on the capital structure. Board size, board independence, and ownership concentration affected the financial performance directly. However, the board's independence, size, and ownership concentration failed to indirectly influence the financial performance. Further, the managerial ownership exhibited no meaningful influence on the financial performance, either directly or indirectly. The findings support that the dimensions of Good Corporate Governance impact firm performance, particularly when interacting with capital structure. The implications are valuable for policymakers and corporate leaders, as they highlight that good governance practices alone may not be sufficient; optimal capital structure strategies must also be incorporated. The findings provide new insights into corporate governance policy by demonstrating its role beyond traditional monitoring, suggesting that governance practices can influence performance when combined with effective capital management strategies. Therefore, the findings enrich the academic discourse by presenting a more thorough perspective on how the corporate governance dimensions relate to capital structure to enhance financial performance.